Research on the influencing factors of the willingness to teach among normal school students: based on Social Cognitive Career Theory - Guo, Jing; Tian, Li Jun (Frontiers in Psychology, 2025)
The willingness to teach among normal school students, especially those majoring in primary education, is an important factor affecting the stability of China’s primary education teaching staff and the quality of the training reserve force of primary education teachers. However, currently, a lack of research exists on the willingness to teach among normal school students majoring in primary education from a dynamic theoretical perspective. This study was based on the Social Cognitive Career Theory (SCCT) model. A questionnaire survey method was used to analyze the willingness to teach and its influencing factors among 630 normal school students majoring in primary education. The results indicated a positive correlation between professional identity, learning satisfaction and willingness to teach among normal school students majoring in primary education, of which the professional identity of the normal school students had a significant positive predictive effect on their willingness to teach. Learning satisfaction partially mediated the relationship between the professional identity and willingness to teach of the normal school students; gender played a moderating role in the relationship between the professional identity and willingness to teach of the normal school students. Studying the influence mechanism of willingness to teach from the perspective of SCCT is of great significance in enhancing the willingness of normal school students majoring in primary education and strengthening the stability of teaching.